2012
DOI: 10.1111/j.1476-5381.2011.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of renal ischaemia–reperfusion injury by liposomal delivery of curcumin to renal tubular epithelial and antigen‐presenting cells

Abstract: BACKGROUND AND PURPOSERenal ischaemia-reperfusion (IR) injury is an inevitable consequence of renal transplantation, causing significant graft injury, increasing the risk of rejection and contributing to poor long-term graft outcome. Renal injury is mediated by cytokine and chemokine synthesis, inflammation and oxidative stress resulting from activation of the NF-kB pathway. EXPERIMENTAL APPROACHWe utilized liposomal incorporation of a potent inhibitor of the NF-kB pathway, curcumin, to target delivery to rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 59 publications
3
40
0
1
Order By: Relevance
“…On the other hand, recent studies have revealed that the antiapoptotic properties of curcumin against acute renal injury caused by ischemia/reperfusion 11,15 and gentamicin. 12 In this study, significant increases in serum urea and creatinine levels after exposure to cisplatin were accepted as an indicator of nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, recent studies have revealed that the antiapoptotic properties of curcumin against acute renal injury caused by ischemia/reperfusion 11,15 and gentamicin. 12 In this study, significant increases in serum urea and creatinine levels after exposure to cisplatin were accepted as an indicator of nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Curcumin, a major component of turmeric, is known to have anti-inflammatory and antioxidant effects in various pathologies. [11][12][13][14][15][16][17] In addition, recent studies have revealed that the antiapoptotic properties of curcumin against different agent-mediated acute renal injury. 11,12,15 It has been reported that curcumin prevents and ameliorates the severity of cisplatin nephrotoxicity, by inhibiting various cytokines and chemokines such as TNF-a and IL-1b and scavenging free radicals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between WT and knockout mice may have been greater if observed at an earlier time point (3-6 hours of reperfusion) that reflects the early phase development of apoptosis in IRI, 37 but apoptotic figures are typically evident at 24 hours of reperfusion. 38,39 The role of CD47 in programmed cell death has been defined in T cells through an interaction with BNIP3. 23 The involvement of CD47 in promoting apoptosis in other cell types has not been investigated, but the decreased RTEC apoptosis observed in CD47 2/2 mice may be explained by the proapoptotic function of CD47.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles have the potential to evade recognition and uptake by the reticuloendothelial systems within the body and can flow into the blood for a longer time because of their small size, thereby via particle uptake mechanism drug bioavailability increase [70]. Nanocurcumin has many biological functions like anticancer action [71], anti-inflammatory action [72,73], antioxidative action [74][75][76], antiamyloid action [77,78], antimicrobial action [79], and antifibrotic action. Fibrosis refers to a condition in which the normal fibrous tissues of any organ are replaced by excessive and unnecessary invasion of fibrous connective tissues.…”
Section: Removal Of Lead Toxicity By Nanocurcuminmentioning
confidence: 99%